OTH-10 Therapeutic interleukin 4 modulates monocyte dynamics and accelerates repair following acute liver injury. Issue 2 (June 2019) - Lynch, Ruairi; Bain, Calum; Hawley, Cathy; Forbes, Professor Stuart; Jenkins, Steve
Abstract : Introduction: Acute liver failure has significant mortality, and in its most severe form, the only treatment is liver transplantation. Murine models of acute liver injury are characterised by changes in the hepatic macrophage compartment, with an initial accumulation of pro-inflammatory Ly6C hi monocytes and loss of Kupffer cells, followed by the dominance of recruited pro-reparative Ly6C lo macrophages. Current experimental immunomodulatory therapeutics like MC21 and Cenicriviroc inhibit Ly6C hi monocyte recruitment. In non-hepatic sterile injury models IL-4 is known to promote pro-reparative macrophage functions and IL-4 administered prior to injury with carbon tetrachloride (CCl4 ) has been shown to be hepatoprotective by directly promoting hepatocyte proliferation. We therefore aimed to assess the potential pro-reparative and immunomodulatory effects of therapeutic IL-4 administered following acute liver injury with CCl4 . Methods: Male C57Bl/6 mice were given CCl4 intraperitoneally to induce an acute liver injury. IL-4 was administered in the form of an immune complex subcutaneously. To investigate the role of IL-4Rα signalling in bone marrow derived cells, whole-body and tissue-protected chimeras were generated with wild type or IL-4Rα -/- donor bone marrow. Results were analysed using immunohistochemistry of tissue sections, serum biochemistry and flow cytometric analysis of leukocytes. Results: Therapeutic administration of IL-4 following CCl4 reduced markers of hepatic injury (ALT and necrotic area) and enhanced hepatic regeneration as measured by hepatocyte proliferation. This was paralleled by profound alterations to the monocyte/macrophage pool, with increases in the number of pro-reparative Ly6C lo macrophages but also a significant reduction in the number of pro-inflammatory hepatic Ly6C hi monocytes. Using chimeras, we have shown that Ly6C lo macrophage accumulation required cell-intrinsic, IL-4Rα-dependent proliferation and the loss of hepatic Ly6C hi monocytes was dependent on cell-intrinsic, IL-4Rα signalling. Importantly, analysis of kidney, spleen and blood revealed that the loss of Ly6C hi monocytes secondary to IL-4 treatment was not limited to the liver and occurred systemically. In vitro and ex vivo assays showed that the reduction in Ly6C hi monocytes in response to administration of IL-4 was due to IL-4Rα-dependent apoptosis of circulating monocytes rather than decreased output from the bone marrow. Conclusion: This novel role of IL-4 offers potential therapeutic benefits over monocyte inhibitors by not only reducing pro-inflammatory Ly6C hi monocyte numbers through apoptosis but also increasing the number of pro-reparative Ly6C lo macrophages.